2013
DOI: 10.1080/00071668.2013.791965
|View full text |Cite
|
Sign up to set email alerts
|

The influence of diet composition on egg and chick traits in captive Greater Rhea females

Abstract: 1. This study was conducted to evaluate the influence of diet composition on egg number, physical and chemical characteristics of eggs and weight and survival of chicks throughout a breeding season in a captive-bred population of greater rheas (Rhea americana). 2. From August to December, individuals were offered two diets: processed feed for rheas and processed feed for chicken (which is the feed most commonly offered to farmed rheas in Argentina). Reproductive performance of 15 females was monitored and fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Moreover, our results showed that egg quality (measured in this study as yolk, albumen, and shell weight) did not change between seasons (Table ). In Greater Rheas, diet composition and traits of laying females have been found to influence egg characteristics (Lábaque et al., , ); therefore, the stability that we found in egg quality during the breeding seasons is in accordance with the idea that rearing conditions did not change substantially across the years.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, our results showed that egg quality (measured in this study as yolk, albumen, and shell weight) did not change between seasons (Table ). In Greater Rheas, diet composition and traits of laying females have been found to influence egg characteristics (Lábaque et al., , ); therefore, the stability that we found in egg quality during the breeding seasons is in accordance with the idea that rearing conditions did not change substantially across the years.…”
Section: Resultssupporting
confidence: 89%
“…Lipids were subjected to alkaline saponification (1 mol L −1 potassium hydroxide in methanol), and the unsaponifiable matter was extracted with n ‐hexane. The fatty acid methyl esters (FAMEs) were prepared by transmethylation through treatment with 1 mol L −1 sulfuric acid in methanol and analyzed by gas chromatography/mass spectrometry (GC/MS) according to Labaque et al …”
Section: Methodsmentioning
confidence: 99%
“…Lipids were subjected to alkaline saponification (1 mol L −1 potassium hydroxide in methanol), and the unsaponifiable matter was extracted with n-hexane. The fatty acid methyl esters (FAMEs) were prepared by transmethylation through treatment with 1 mol L −1 sulfuric acid in methanol and analyzed by gas chromatography/mass spectrometry (GC/MS) according to Labaque et al 29 Thin layer chromatography (TLC) on silica gel G, with a hexane/diethyl ether/acetic acid (80:20:1 v/v/v) solvent system, was used to separate the total lipid extract into two of its major fractions (TG and PL) according to the technique described by Royle et al 30 The separated bands were visualized with iodine vapor and identified by comparison with the migration of lipid standards in this system. The bands were scraped from the plates and the lipids were eluted from the silica by vortex mixing with 3 × 5 mL of either chloroform/methanol/water (5:5:1 v/v/v; PL) or diethyl ether (TG).…”
Section: Fatty Acid Analysismentioning
confidence: 99%
“…Lipids were subjected to alkaline saponification (1 mol/L potassium hydroxide in methanol), and the unsaponifiable matter was extracted with n-hexane. The fatty acid methyl esters (FAMEs) were prepared by transmethylation through treatment with 1 mol/L sulfuric acid in methanol and analyzed by gas chromatography/mass spectrometry (GC/MS) [16,44]. All chemicals used in this study were reagent-grade commercial products.…”
Section: Total Fatty Acid Analysis In Egg Yolksmentioning
confidence: 99%